2013
DOI: 10.1007/s10530-013-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of weed invasion: evidence from the spatial genetic structure of Raphanus raphanistrum

Abstract: Knowledge of the pathways of colonization is critical for risk assessment and management of weeds. In this study we adopted a landscape genetics approach to assess the impact of human disturbances and large-scale environmental features on the colonization of a global agricultural weed, Raphanus raphanistrum. We used nuclear microsatellite and chloroplast DNA sequence data to quantify the pattern of genetic diversity in 336 plants collected from 13 sites throughout the Cape Floristic Region, South Africa, one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…we differ in this conclusion (Cousens et al, 2013) from Cody & Cody (2004)) and there is no longer any evidence of genome mixing detectable in the nuclear microsatellite data. Foreign chloroplast frequencies can be close to 50% or higher, as has been found with Raphanus sativus introgression into R. raphanistrum (Barnaud et al, 2013). Most neutral C. edentula traits determined by nuclear genes will disappear after only a few generations of back-crossing to C. maritima (pollinators are attracted more to C. maritima than to C. edentula: Rodman, 1974).…”
Section: Discussionmentioning
confidence: 74%
“…we differ in this conclusion (Cousens et al, 2013) from Cody & Cody (2004)) and there is no longer any evidence of genome mixing detectable in the nuclear microsatellite data. Foreign chloroplast frequencies can be close to 50% or higher, as has been found with Raphanus sativus introgression into R. raphanistrum (Barnaud et al, 2013). Most neutral C. edentula traits determined by nuclear genes will disappear after only a few generations of back-crossing to C. maritima (pollinators are attracted more to C. maritima than to C. edentula: Rodman, 1974).…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, chloroplast DNA (cpDNA) is inherited maternally in angiosperms. It is used to detect the maternal parents of hybrids (Bleeker, 2003;Muranishi et al, 2013) and also in studies of invasions (Bleeker, 2003;Gaskin et al, 2005;Barnaud et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wild radish has successfully colonized a variety of locations, leading to its naturalization on all continents except Antarctica (Holm, Doll, Holm, Pancho, & Herberger, ), and it is often a major agricultural weed (Sahli, Conner, Shaw, Howe, & Lale, ; Warwick & Francis, ). Studies on the geographic distribution of the genetic variability and morphological traits of wild radish have shown that divergence between populations does not correspond to a geographic pattern that can be attributed to isolation distance (Barnaud, Kalwij, McGeoch, & van Vuuren, ; Kercher & Conner, ; Sahli et al, ; Tokunaga & Ohnishi, ). Kercher and Conner () have suggested three possible explanations for this observation: (a) wild radish self‐incompatibility promotes gene flow, (b) radish seeds can disperse over long distances, and (c) introgression occurs from the cultivated radish ( R. sativus ).…”
Section: Introductionmentioning
confidence: 99%